Efek Pemberian Tepung Limbah Tauge dalam Ransum Terhadap Bobot Telur dan Produksi Telur Puyuh (Cortunix-Cortunix Japonica) - Muhammad Jurhadi Kadir; Ahsan Ahsan; Irmayani Irmayani (bionature, 2022)
Abstract. This study aims to determine the effect of giving bean sprouts with different levels in the ration on egg production and quail egg weight. Using a completely randomized design (CRD) with 4 treatment levels and 3 replications so that there were 12 units of observation, each experimental unit consisted of 10 quails with a total of 120 quails. Each treatment consisted of P0: ration without bean sprouts waste (control), P1: ration with 3% bean sprouts waste, P2: ration with 6% bean sprouts waste, P3: ration with 8% bean sprouts waste. The results of variance showed that the addition of bean sprouts at different levels had a significant effect (p≤0.05) on egg production and a very significant effect (p≤0.01) on quail egg weight. The average quail egg production ranged from 70.83% - 94.17%, while the average quail egg weight ranged from 11.73% - 12.64%. It was concluded that the provision of bean sprouts waste flour in quail rations with a concentration of 3% gave the best effect on egg production and quail egg weight (Coturnix-coturnix japonica). Keywords: bean sprout waste flour, egg production, egg weight, quail eggs